Do Largo das Mercês à Praça Visconde do Rio Branco: um estudo de gestão do patrimônio histórico em Belém do Pará, 1941-2011 - BORGES, Tatiana Carepa Roffé (Universidade Federal do Pará, 2014)
Do Largo das Mercês à Praça Visconde do Rio Branco: um estudo de gestão do patrimônio Histórico em Belém do Pará, 1941-2011, proposes to conduct an analysis of the management of organ preservation at the local, state and federal in Belém, Pará, from a study on the square and immediate surroundings (houses surrounding it) in order to observe the evolution of the characterization and conservation of the architectural, urban and landscape from the 1940s to the present day. The visual language of this dissertation allows the observation of the changes and continuities that occurred in the square and bounding properties, since the photographic image, as well as other sources and visual objects, is in important historical research tools to identify new objects and new problems and indicating those that remain over the years. It is intended that the analysis of the current characterization of the set, compared with the same configuration at the time of their respective legal protection indicate how the organ preservation’s work is being done to protect the cultural heritage, checking for compatibility criteria and actions, and ownership of the square by society. This study also seeks to diagnose the current problems of the square and the importance of maintenance for the architectural and historical memory of the city Belém.